2014
DOI: 10.1021/nl502156h
|View full text |Cite
|
Sign up to set email alerts
|

Crossed Ga2O3/SnO2 Multiwire Architecture: A Local Structure Study with Nanometer Resolution

Abstract: Crossed nanowire structures are the basis for high-density integration of a variety of nanodevices. Owing to the critical role of nanowires intersections in creating hybrid architectures, it has become a challenge to investigate the local structure in crossing points in metal oxide nanowires. Thus, if intentionally grown crossed nanowires are well-patterned, an ideal model to study the junction is formed. By combining electron and synchrotron beam nanoprobes, we show here experimental evidence of the role of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
(84 reference statements)
1
27
0
Order By: Relevance
“…The change and shifted energies of white-line feature can be attributed mainly to the disordered and different coordination environments 20 . In addition, the negative shift of the adsorption edge occurs with decreased coordination, which can be used as an indicator of the coordination number of O atom in the structure 21 . The Fourier transform EXAFS spectra of Ga K-edge were used to further understand the atomic structure of ZnGa 2 O 4 film.…”
Section: Resultsmentioning
confidence: 99%
“…The change and shifted energies of white-line feature can be attributed mainly to the disordered and different coordination environments 20 . In addition, the negative shift of the adsorption edge occurs with decreased coordination, which can be used as an indicator of the coordination number of O atom in the structure 21 . The Fourier transform EXAFS spectra of Ga K-edge were used to further understand the atomic structure of ZnGa 2 O 4 film.…”
Section: Resultsmentioning
confidence: 99%
“…The anisotropy of monoclinic gallium-oxide crystal lattice leads to the spontaneous growth of microwires by thermal evaporation methods with an optimal aspect ratio for effective light waveguiding. Furthermore, we have previously reported the formation of more-complex morphologies, such as branches or crossed wires, by codoping Ga 2 O 3 with Sn and Cr [43][44][45]. On the other hand, the high crystal quality and smooth lateral-wall surface of Ga 2 O 3 ∶Cr microwires enables some light confinement and we demonstrate Fabry-Perot resonances due to the reflection in their two ends, because of the refractiveindex change between the material and the air [42].…”
Section: Introductionmentioning
confidence: 66%
“…transversal pyramids that grow on the lateral sides of the main rods. It has been previously reported that during vapour-solid (VS) growth the presence of different doping elements in the precursors can result in notable morphological changes, such as the formation of branches [9], crossing wires [17] and complex hierarchical structures [18]. However, these morphological pyramidal features have not been observed with other dopants or in undoped gallium oxide microstructures grown under similar conditions, as shown in figure 1(e).…”
Section: Methodsmentioning
confidence: 93%